Open and Arthroscopic with Mini-Open Surgical Hip Approaches for Treatment of Pigmented Villonodular Synovitis and Concomitant Hip Pathology - Bridget Ellsworth; Atul F. Kamath (Case Reports in Orthopedics)
Background. Pigmented villonodular synovitis (PVNS) is a rare benign tumor affecting large joints and prompts excision to prevent local destruction of the joint. The purpose of this case report is to describe two differing surgical approaches for management of PVNS of the hip in patients requiring concomitant treatment for additional hip pathology. Methods. This report discusses the presentation, clinical and radiographic findings, and operative management of two contrasting cases of PVNS of the hip. Case 1 describes a 31-year-old female with localized PVNS in addition to a labral tear treated with arthroscopic labral repair followed by tumor excision via a mini-open incision. Case 2 describes a 29-year-old male with more diffuse PVNS in addition to a cam deformity managed with open surgical dislocation of the hip, tumor excision, and restoration of the femoral head/neck junction. Results. This report demonstrates two cases of successful excision of PVNS of the hip in addition to addressing concomitant hip pathology in both cases. Conclusions. Open surgical dislocation of the hip or arthroscopic surgery with a mini-open incision may be used in appropriately selected patients to successfully excise PVNS lesions in addition to addressing concomitant hip pathology.